Pengaruh Keterlibatan Ayah Dalam Pengasuhan Terhadap Konsep Diri Remaja di Masyarakat Batak - Ega Valenia Situmorang; Zuhdi Budiman (Universitas Medan Area, 2022)
The purpose of this study was to examine the effect of father involvement in parenting on adolescent self- concept in the Batak Toba community in Untemungkur II Village. The hypothesis is that there is a positive influence between father's involvement in parenting on self-concept. The subjects of this study were teenagers aged 12-20 years in Untemungkur II Village as many as 70 people. The method of data analysis is a simple linear regression test. The results of the research, the t-count coefficient is 5.655, with a significance value of pp 0.01, then the hypothesis in this study is accepted, in the sense that there is an influence of father's involvement with self-concept, with the magnitude of the influence in linear form can be written as follows: y = 42,292 + 0.516* (X). This means that the magnitude of the influence of father's involvement on self-concept is 42.808.